PENGARUH ENTREPRENEURIAL MARKETING, INNOVATION, DAN COSTUMER EXPERIENCE TERHADAP KINERJA PEMASARAN JASA LAUNDRY DI YOGYAKARTA - Putriningtyas, Siwi; Nasution, Mulyadi Arjun; Dewi, Septiana Novita (STIE AUB Surakarta, 2018)
Research this aim for analyze influence entrepreneurial marketing, innovation, and customer experience to performance marketing laundry services in Yogyakarta. Method taking sample using simple random sampling. Method The analysis is analysis qualitative in kuantitatifkan with use test validity, reliability, test assumption classic, Multiple linear test, t test, F test, and coefficient determination. With use method regression multiple could concluded that variable entrepreneurial marketing, innovation, and customer experience take effect significant to performance marketing laundry services in Yogyakarta. With use t test can is known that all variable bepengaruh positive and significantly. Coofisien The resulting determination is of 0.364 which means that 36, 4% were able to explained by variable entrepreneurial marketing, innovation, and customer experience on together. Keywords: Entrepreneurial Marketing, Innovation, and Customer Experience, Performance Marketing.